THE ROLE OF PAREMIAS IN LANGUAGE AND CULTURE - Khudaybergenova Gulbakhor (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article examines the role of paremias, such as proverbs, sayings, and idioms, in both the Uzbek and English languages, focusing on their linguistic and cultural significance. Paremias are short, fixed expressions that convey cultural wisdom, moral lessons, and social norms. Through a comparison of both languages, the article explores how these expressions reflect the values, traditions, and worldviews of their respective societies. The study highlights the linguistic features of paremias, their function in communication, and their cultural importance in shaping societal norms and reinforcing social values. The research also emphasizes the role of paremias as tools for communication, providing succinct, culturally rich expressions that reflect the worldview of different communities.